2009
DOI: 10.1253/circj.cj-09-0327
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eicosapentaenoic Acid and Docosahexaenoic Acid as Predictors of All-Cause Mortality in Patients With Acute Myocardial Infarction Data From Infarction Prognosis Study (IPS) Registry

Abstract: Background: Although ω-3 polyunsaturated fatty acids are known to have beneficial effects on cardiovascular diseases, their prognostic value has not been studied prospectively in patients with acute myocardial infarction (AMI). Methods and Results:The plasma levels of phospholipids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) (% of total fatty acids), were measured in 508 patients (365 males; mean age, 63 years) with AMI. Clinical and biomarker predictors of all-cause and cardiovascular mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 36 publications
7
23
0
Order By: Relevance
“…33 It is also reported that a low plasma level of EPA, but not DHA, was an independent predictor for all-cause mortality in patients with acute myocardial infarction. 34 The results of those reports are consistent with our CTA results that a low EPA level, but not low DHA, was associated with coronary plaque findings, especially the presence, extent, and characteristics of NCPs.…”
Section: Difference In Effects Of Serum Epa and Dhasupporting
confidence: 90%
“…33 It is also reported that a low plasma level of EPA, but not DHA, was an independent predictor for all-cause mortality in patients with acute myocardial infarction. 34 The results of those reports are consistent with our CTA results that a low EPA level, but not low DHA, was associated with coronary plaque findings, especially the presence, extent, and characteristics of NCPs.…”
Section: Difference In Effects Of Serum Epa and Dhasupporting
confidence: 90%
“…With respect to cardiovascular death, the blood EPA HR was 0.41 (p = 0.005) and the blood DHA HR was 0.84. This finding demonstrates that higher EPA levels are associated with a reduction in the incidence of cardiovascular death in myocardial infarction patients 23) . Domei et al reported that univariate analyses of hazardous cardiac events in patients undergoing percutaneous coronary intervention (PCI) yielded an HR of 0.54 (p= 0.031) for blood EPA, 0.59 (p= 0.060) for DHA, 0.50 (p = 0.013) for the EPA/AA ratio and 0.65 (p=0.127) for the DHA/AA ratio, indicating that higher EPA levels or EPA/AA ratios, but not DHA levels or DHA/AA ratios, are associated with a reduction in the incidence of hazardous cardiac events 24) .…”
Section: Effects Of the Administration Of Fish Oil Or High-purity Epamentioning
confidence: 59%
“…30 Similarly, in Korean acute myocardial infarction patients, an EPA+DHA >4.74% was associated with reduced all-cause and CVD mortality, and a low EPA (<1.26%) was associated with high risk. 51 In JELIS, CHD patients an EPA/AA ratios >1.06 was associated with the lowest cardiac death or myocardial infarction rates, and major coronary events were significantly reduced with EPA treatment (P=0.048). 25,48 In the peripheral artery disease population, EPA supplementation reduced major coronary events 55% in comparison with 18% in the non-peripheral artery disease group, and the number needed to treat was 11 with the blood level of EPA increasing from a mean of 2.8 to 5.6 mol%.…”
Section: Secondary Prevention and Peripheral Vascular Diseasementioning
confidence: 90%